(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
The evolution of temple architecture in Himachal Pradesh represents a vibrant interaction between spiritual devotion, cultural transformations, and environmental influences, culminating in unique architectural styles that have evolved over centuries. The temple architecture in Himachal Pradesh is characterized by two prominent typologies: the Nagara temple architecture including Latina form, and a distinctive Himalayan style marked by pyramidal and conical roofs, utilizing composite materials such as wood and stone. This systematic review examines the evolution from early stone temples to hybrid wood–stone structures. By reviewing scholarly literature, archival records, and regional studies, we identify key trends in construction techniques and stylistic adaptations. The findings reveal that local environmental challenges (e.g., seismic activity and harsh climates) have driven innovations such as the Kath-Khuni technique, while external influences have contributed to a diverse architectural vocabulary. While construction techniques, materials, and design approaches vary across different sites, some temples display a synthesis of architectural styles, highlighting a shared heritage. This review also highlights research gaps in interdisciplinary analysis, computational modeling, and conservation science, suggesting avenues for future inquiry.